Overview of Electric Motor Technologies Used for More Electric Aircraft (MEA) - Wenping Cao; Mecrow, B. C.; Atkinson, G. J.; Bennett, J. W.; Atkinson, D. J. (IEEE transactions on industrial electronics (1982), 2012)
This paper presents an overview of motor drive technologies used for safety-critical aerospace applications, with a particular focus placed on the choice of candidate machines and their drive topologies. Aircraft applications demand high reliability, high availability, and high power density while aiming to reduce weight, complexity, fuel consumption, operational costs, and environmental impact. New electric driven systems can meet these requirements and also provide significant technical and economic improvements over conventional mechanical, hydraulic, or pneumatic systems. Fault-tolerant motor drives can be achieved by partitioning and redundancy through the use of multichannel three-phase systems or multiple single-phase modules. Analytical methods are adopted to compare caged induction, reluctance, and PM motor technologies and their relative merits. The analysis suggests that the dual (or triple) three-phase PMAC motor drive may be a favored choice for general aerospace applications, striking a balance between necessary redundancy and undue complexity, while maintaining a balanced operation following a failure. The modular single-phase approach offers a good compromise between size and complexity but suffers from high total harmonic distortion of the supply and high torque ripple when faulted. For each specific aircraft application, a parametrical optimization of the suitable motor configuration is needed through a coupled electromagnetic and thermal analysis, and should be verified by finite-element analysis.